Treatment with Commelina communis Extract Exerts Anti-inflammatory Effects in Murine Macrophages via Modulation of the Nuclear Factor-κB Pathway - Kim, Ji-Hee; Park, Bog-Im; You, Yong-Ouk (Mediators of Inflammation, 2022)
The incidence of severe inflammatory diseases caused by chronic inflammation has increased owing to unprecedented changes brought about by industrialization. In this study, we aimed to assess the effect of treatment of lipopolysaccharide- (LPS-) induced murine macrophages with Commelina communis Linne extract (CCE) on synthesis of nitric oxide (NO), hypersecretion of proinflammatory cytokines, intranuclear transition of the p65 subunit of nuclear factor- (NF-) κB, and degradation of the NF-κB inhibitor IκBα. Notably, CCE treatment did not affect cell viability even at a final concentration of 1.5 mg/mL. At a high concentration of CCE, the LPS-induced high levels of NO, tumor necrosis factor-α, interleukin- (IL-) 1β, and IL-6 were decreased via downregulation of inducible NO synthase and proinflammatory cytokine mRNA expression. Furthermore, phosphorylation of IκBα was significantly decreased upon CCE treatment, and the intranuclear transition of NF-κB p65 triggered by LPS was inhibited at a high concentration of CCE. Polyphenols and flavonoids, secondary metabolites in CCE that regulate the NF-κB pathway, may be responsible for its anti-inflammatory activity. We suggest that CCE has anti-inflammatory effects related to suppression of the NF-κB pathway and can be used to treat chronic inflammation.